Studies on The Breakdown of Male Sterility In Some Male Sterile Lines of Pearl Millet (Pennisetum typhoides) Under Conditions of Arid Zone - Saxena, M B L; Chaudhary, B S (Annals of Arid Zone, 2016)
The expression of stability in eight male sterile lines of bajra in relation with temperature, relative humidity, day length and rainfall were studied during kharif 1974 and 1975. M.S. lines 23D2A, 1OIA, 111A and 239D2A,gave out pollen shedders and the frequency was very low in the second year. Correlations for temperature (positive) and relative humidity (negative) with pollen shedding plants were found significant. Negative correlations for day length and rainfall were"however, non significant.